The Influence of Online Learning on Students' Level of Understanding in Courses of Quantitative Research Methods KPI2 Class - Ramadhani Ramadhani; Ika Fitrah Dayanti; Annisa Nur Ramadhani; Putri Hidayani; Andi Dian Fitriana; Sulvinajayanti Sulvinajayanti (State Islamic Institute of Bone, Indonesia, 2022)
This study aims to determine the understanding of students during the online lecture learning (online) in the quantitative research method of the KPI2 Class IAIN Parepare. Meanwhile researchers use ex post facto research design which is part of the quantitative method. As for getting data used the primary data collection techniques in the form of questionnaires and documentation. With a population of 40 KPI class students of the quantitative research method course and the sample number of 28 students. Based on the results of research that has been collected through the spread of questionnaires, (1) 60.7% of respondents answeredthat they do not like online learning, while 39.2% of them like online-based learning, (2) 71.4% agree that online courses facilitate the lecture process, while 28.5% disagree with the statement, (3) 60.7% disagree with online courses for quantitative research method courses, while 39.2% agree with the statement, (4) 57.1% agreed with the use of Zoom and WhatsApp apps, while 42.8% agreed. So it was concluded that the influence of online lectures on students' understanding in the quantitative research method courses of KPI2 classes entered the moderate category. Keyword: Online, Understanding, Quantitative Lectures